Disrupting cholesterol esterification by bitter melon suppresses triple‐negative breast cancer cell growth. Issue 11 (26th August 2018) - Shim, So Hee; Sur, Subhayan; Steele, Robert; Albert, Carolyn J.; Huang, Chunfa; Ford, David A.; Ray, Ratna B.
Abstract : Triple negative breast cancer (TNBC) is aggressive with a worse prognosis. We have recently shown that bitter melon extract (BME) treatment was more effective in inhibition of TNBC tumor growth in mouse models as compared to ER positive breast tumor growth. Aberrant dysregulation of lipid metabolism is associated with breast cancer progression, however, anti‐cancer mechanism of BME linking lipid metabolism in breast cancer growth remains unexplored. Here, we observed that accumulation of esterified cholesterol was reduced in BME treated TNBC cell lines as compared to control cells. We next evaluated expression levels of acyl‐CoA: cholesterol acyltransferase 1 (ACAT‐1) in TNBC cells treated with BME. Our results demonstrated that BME treatment inhibited ACAT‐1 expression in TNBC cells. Subsequently, we found that sterol regulatory element‐binding proteins‐1 and ‐2, and FASN was significantly reduced in BME treated TNBC cell lines. Low‐density lipoprotein receptor was also downregulated in BME treated TNBC cells as compared to control cells. We further demonstrated that BME feeding reduced tumor growth in TNBC mammospheres implanted into NSG mice, and inhibits ACAT‐1 expression. To our knowledge, this is the first report demonstrating BME suppresses TNBC cell growth through ACAT‐1 inhibition, and have potential for additional therapeutic regimen against human breast cancer.